Imaging the Centromedian Thalamic Nucleus Using Quantitative Susceptibility Mapping - Li, Jun; Li, Yufei; Gutierrez, Lorenzo; Xu, Wenying; Wu, Yiwen; Liu, Chunlei; Li, Dianyou; Sun, Bomin; Zhang, Chencheng; Wei, Hongjiang (Frontiers in Human Neuroscience, 2020)
The centromedian (CM) nucleus is an intralaminar thalamic nucleus which is considered as a potentially effective target of deep brain stimulation (DBS) and ablative surgeries for the treatment of multiple neurological and psychiatric disorders. However, the structure of CM is invisible on the standard T1- and T2-weighted (T1w and T2w) magnetic resonance images which hamper it as a direct DBS target for clinical applications. The purpose of the current study is to demonstrate the use of quantitative susceptibility mapping (QSM) technique to image the CM within the thalamic region. 12 patients with Parkinson’s disease, dystonia or schizophrenia were included in this study. A 3D multi-echo gradient recalled echo (GRE) sequence was acquired together with T1w and T2w images on a 3T MR scanner. The QSM image was reconstructed from the GRE phase data. Direct visual inspection of the CM was made on T1w, T2w and QSM images. Furthermore, the contrast-to-noise ratios (CNRs) of the CM to the adjacent posterior part of thalamus on T1w, T2w and QSM images were compared using the one-way analysis of variance test. QSM dramatically improved the visualization of the CM nucleus. Clear delineation of CM compared to the surroundings was observed on QSM but not on T1w and T2w images. Statistical analysis showed that the CNR on QSM was significantly higher than those on T1w and T2w images. Taken together, our results indicate that QSM is a promising technique for improving the visualization of CM as a direct targeting for DBS surgery.